Growth Response, Serum Biochemistry and Organ Histopathology of Broilers Fed Diets supplemented with Graded levels of Petiveria alliacea Root Meal - Odetola , Olubayo M.; Adejinmi, Olufunmilayo O.; Owosibo, Olatunde A.; Banjo, Omotoyosi T.; Awodola-Peters, Omolade O. (International Journal of Poultry Science, 2018)
Background and Objective: This study was conducted to assess the growth response, serum biochemistry and organ histopathology of broiler chickens. Materials and Methods: A total of 180 unsexed day old broiler chickens were used for this study. Broiler chickens fed diets supplemented with graded levels of Petiveria alliacea root meal (PRM) at 0, 500, 1000, 1500, 2000 and 2500 g/100 kg of feed in 8 weeks feeding trial. Data were collected on feed intake and weekly weight gain. Blood samples were collected from the animals through the wing web vein for serum biochemistry while samples of visceral organs and small intestine were collected from the animals after they were stunned and sacrificed. Results: Results revealed no significant difference (p>0.05) in all the growth response parameters examined. While Aspartate amino transferase were significantly (p<0.05) lower in T6, glucose and cholesterol of the experimental birds were significantly higher in T6 (p<0.05). Relative organ weight of various visceral organs examined apart lung, kidney and spleen were also significantly influenced by the dietary treatments. The results of histopathological examination revealed damages done by dietary treatments. Necrosis of the villi and tubular epithelium were observed in intestine and kidney in all the treatment except the control. The liver of bird fed PRM showed signs of hepatocellular necrosis and increased mononuclear/inflammatory cells in the hepatocyte, which increased as the inclusion of PRM increased. Conclusion: Petiveria alliacea root meal as a phytobiotics improved the growth performance of broiler chicken, does not have any negative effects on the serum biochemistry but may induce necrosis of the villi and hepatocytes if fed above 1500 g/100 kg of feed for a longer period of time.